Staff and service users’ views on a ‘Consent for Contact’ research register within psychosis services: a qualitative study - Papoulias, Constantina (BMC Psychiatry, 2014)
BACKGROUND: Recruitment to mental health research can be challenging. ‘Consent for Contact’ (C4C) is a novel framework which may expedite recruitment and contribute to equitable access to research. This paper discusses stakeholder perspectives on using a C4C model in services for people with psychosis. METHOD: This is a cross sectional study investigating the views of service users and staff using qualitative methods. Eight focus groups were recruited: five with service users (n = 26) and three with clinicians (n = 17). Purposive sampling was applied in order to reflect the local population in terms of ethnicity, experience of psychiatric services and attitudes towards research. RESULTS: Staff and service users alike associated the principle of ‘consent for contact’ with greater service user autonomy and favourable conditions for research recruitment. Fears around coercion and inappropriate uses of clinical records were common and most marked in service users identifying as having a negative view to research participation. Staff working in inpatient services reported that consenting for future contact might contribute to paranoid ideation. All groups agreed that implementation should highlight safeguards and the opt-in nature of the register. CONCLUSIONS: Staff and service users responded positively to C4C. Clinicians explaining C4C to service users should allay anxieties around coercion, degree of commitment, and use of records. For some service users, researcher access to records is likely to be the most challenging aspect of the consultation.